PROFESIONALISASI KPEMIMPINAN UNTUK MENGATASI KONFLIK ORGANISASI TERHADAP KINERJA ORGANISASI - Pribadi Widyatmojo (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2012)
Very common the leader, using his or her power, subjectively justify that his or her subordinates are not fit enough with the organization’s performance standards. In fact the performance measurement is no only aplicable the staff or subordinates, but also to the leaders his or herself. This article is proposing the new way of measuring the performance of staff or subordinates as well as the leaders. This article proposing the balance justification of performance to both staff or subordinate and leaders. This article emphasized on the new ways in measuring the staff and leader fitness to organization as well as the conflict management among the leaders and other professional element in the organization.Keywords: leader, staff or subordinate, performance measurement, conflict management.